Electron energy bands of CdO crystal evaluated with accounting of the strong correlated electrons - Syrotyuk, S.; Shved, V. (Видавництво Львівської політехніки, 2012)
The electron energy bands and densities of states have been calculated within the projector augmented waves (PAW) formalism. The PBE exchange-correlation functional gives the absence of the gap contrary to the experiment. The account of the exact exchange substantially improves the results for direct and indirect interband gaps.
Keywords: electronic structure calculations; strongly correlated electrons; exact exchange for correlated electrons; projector augmented wave method